Festival Jelajah Maumere (FJM) sebagai Media Promosi Tenun Ikat di Kabupaten Sikka Provinsi NTT - Kurnyati, Arlinda Icha; Retu, Markus Kristian; Mustafa, Intan (Fakultas Ilmu Budaya, Universitas Jambi, 2024)
The aim of this research is to find out and describe how the Maumere Exploration Festival (FJM) is a promotional medium for ikat weaving in Sikka Regency. Data collection methods use observation and interviews as well as documentation. Data analysis uses descriptive analysis. Data validity checking techniques use triangulation of sources and methods. The results of the research concluded that there are 3 roles of the Maumere Exploration Festival as a promotional medium for ikat weaving in Sikka Regency, namely 1) FJM as an educational event and introduction to ikat weaving. Visitors have the opportunity to experience the ikat weaving process first hand, from thread preparation, dyeing, to the complex weaving process that requires advanced techniques. 2) Promotion of ikat weaving as local cultural heritage. Through exhibitions and cultural discussions, visitors are given an understanding of the importance of maintaining the continuity and preservation of weaving traditions. 3) Improve the image of Sikka Regency's ikat weaving by displaying various types of ikat products, both in the form of traditional fabrics and derivative products such as bags, scarves and accessories. Abstract Tujuan dari penelitian ini adalah untuk mengetahui dan mendeskripsikan bagaimana Festival Jelajah Maumere (FJM) sebagai media promosi tenun ikat di Kabupaten Sikka. Metode pengumpulan data menggunakan observasi dan wawancara serta dokumentasi. Analisis data menggunakan analisis deskriptif. Teknik pemeriksaan keabsahan data menggunakan triangulasi sumber dan metode. Hasil penelitian menyimpulkan bahwa terdapat 3 peran Festival Jelajah Maumere sebagai media promosi tenun ikat di Kabupaten Sikka, yakni 1) FJM sebagai ajang edukasi dan pengenalan tenun ikat. Pengunjung berkesempatan untuk merasakan langsung proses pengerjaan tenun ikat, mulai dari persiapan benang, pewarnaan, hingga proses tenun yang rumit yang membutuhkan teknik tinggi. 2) Promosi tenun ikat sebagai warisan budaya lokal. Melalui pameran dan diskusi budaya, pengunjung diberi pemahaman tentang pentingnya menjaga keberlanjutan dan kelestarian tradisi menenun. 3) Meningkatkan citra tenun ikat Kabupaten Sikka dengan menampilkan berbagai jenis produk tenun ikat, baik dalam bentuk kain tradisional maupun produk-produk turunan seperti tas, selendang, dan aksesoris.